2007
DOI: 10.1038/nri2103
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and cooperative antigen-presenting functions of dendritic-cell subsets in vivo

Abstract: Dendritic cells (DCs) comprise several subsets, and their roles in the presentation of antigens derived from pathogens, vaccines and self tissues are now beginning to be elucidated. Differences in location, life cycle and intrinsic abilities to capture, process and present antigens on their MHC class I and class II molecules enable each DC subset to have distinct roles in immunity to infection and in the maintenance of self tolerance. Unexpected interactions among DC subsets have also been revealed. These inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
546
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 569 publications
(584 citation statements)
references
References 138 publications
8
546
1
6
Order By: Relevance
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] DCs are represented by two major lineages, classical or conventional DCs (cDCs) and plasmacytoid DCs (pDCs). [1][2][3] cDCs have outstanding capacity to prime naive T cells to generate various types of effector T (T eff ) cells owing to the prominent expression of major histocompatibility complex class (MHC) II and costimulatory molecues. [4][5][6] On the other hand, pDCs are specialized in endosomal TLR7/9-mediated recognition of viral nucleic acids (NAs) and respond with the massive secretion of type I interferon (IFN-I).…”
Section: Introductionmentioning
confidence: 99%
“…by inducing preferentially CD4 1 or CD8 1 T-cell responses or by inducing innate immunity against pathogens [4,5]. Langerhans cells (LCs) are a subset of DCs that are, in humans, characterized by expression of CD1a, the C-type lectin Langerin and the presence of Birbeck granules [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we demonstrated that DCs require the participation of macrophages to generate protective immune responses against Lm infection and macrophage-released MPs act as a vector to bridge DCs and macrophages. DCs are believed to be specialized in capturing and processing antigens in vivo, 32,33 converting protein antigens to peptides that are presented on MHC molecules and recognized by T cells. Through interactions with DCs, helper T cells differentiate into either Th1 cells, which produce IFN-c to resist infection by facultative and obligate intracellular microbes such as Lm, Th2 cells that produce IL-4 and IL-13 to mobilize immune cells to resist helminths, or Th17 cells producing IL-17 and IL-22 to mobilize phagocytic cells to eliminate …”
Section: Discussionmentioning
confidence: 99%